Sistema de superação e capacitação para prevenção do crime migratório em Angola - António, Angelino José (2018)
The overcoming and qualification of the cadres are, at present, one of the main processes that conceived in the strategy of overcoming and qualification carried out by the Ministry of Interior in Angola, in the development of its missions until by the changes and transformations of political, economic, and social order which are now known in Angolan society. In fact, the present study constitutes a simple contribution particularly for the professionals of the Ministry of the Interior (MININT), especially those of the Migration and Foreigners Services (SME), regarding the legal knowledge in a particular way, in the processes of overcoming and qualifying their staff that is necessary to successfully achieve the goals they propose. In fact, the improvement of the professional and human quality of the cadres through the implementation of the system of overcoming and training for legal education is an important and even preponderant factor to guarantee the efficiency and effectiveness of state actions in the field of state security. Our proposal focuses on the bases of humanistic realism, the theory of systems of overcoming and qualification, that is, an advanced education using different methods of the commonly used (audiovisual) as a goal to teach.